THE INFLUENCE OF SOCIAL MEDIA MARKETING AND SERVICE QUALITY ON VIEWERS OF THE TVRI CHANNEL PROGRAM OF SOUTH SULAWESI - Patwa, Nur Aliyah; Tawe , Amiruddin; Musa , Muh. Ichwan; Sahabuddin , Romansyah; Darmawan Natsir , Uhud (JOURNAL OF HUMANITIES, SOCIAL SCIENCES AND BUSINESS, 2023)
Social media marketing has emerged as a powerful tool for expanding the reach and visibility of TV programs, allowing them to connect with a broader audience. In addition to this, providing high-quality content and ensuring a positive viewing experience can play a pivotal role in increasing viewer satisfaction, fostering loyalty, and encouraging word-of-mouth recommendations. This study aims to investigate the impact of social media marketing and service quality on viewer loyalty towards the South Sulawesi TVRI Event Program, both partially and simultaneously. The study involved a sample of 99 participants who were followers of the Instagram social media account @tvri.sulawesi.selatan. Data was collected through questionnaires, interviews, and observations. The analysis encompassed validity tests, reliability tests, and classical assumption tests, including normality tests, multicollinearity tests, and heteroscedasticity tests. The hypothesis testing comprised of simultaneous tests, partial tests, determination tests, and multiple linear regression tests. The results of the study revealed three significant findings: Firstly, social media marketing variables had a positive and notable effect on audience loyalty. By effectively utilizing social media marketing strategies, the South Sulawesi TVRI Event Program was able to bolster its audience loyalty. Secondly, service quality variables displayed a positive and significant impact on audience loyalty. When the TV program delivered services that met or exceeded viewer expectations, it resulted in heightened levels of audience loyalty. Lastly, the study demonstrated that social media marketing and service quality, when considered together, had a simultaneous positive and considerable effect on audience loyalty. The integration of both aspects contributed to a more profound impact on viewer loyalty.